Occupational Exposure to Antineoplastic Drugs: Identification of Job Categories Potentially Exposed throughout the Hospital Medication System - Chun-Yip Hon; Kay Teschke; Prescillia Chua; Scott Venners; Lynne Nakashima (Safety and Health at Work, 2011)
Objectives: Studies examining healthcare workers’ exposure to antineoplastic drugs have focused on the drug preparation or drug administration areas. However, such an approach has probably underestimated the overall exposure risk as the drugs need to be delivered to the facility, transported internally and then disposed. The objective of this study is to determine whether drug contamination occurs throughout a facility and, simultaneously, to identify those job categories that are potentially exposed. Methods: This was a multi-site study based in Vancouver, British Columbia. Interviews were conducted to determine the departments where the drugs travel. Subsequent site observations were performed to ascertain those surfaces which frequently came into contact with antineoplastic drugs and to determine the job categories which are likely to contact these surfaces. Wipe samples were collected to quantify surface contamination. Results: Surface contamination was found in all six stages of the hospital medication system. Job categories consistently found to be at risk of exposure were nurses, pharmacists, pharmacy technicians, and pharmacy receivers. Up to 11 job categories per site may be at risk of exposure at some point during the hospital medication system. Conclusion: We found drug contamination on select surfaces at every stage of the medication system, which indicates the existence of an exposure potential throughout the facility. Our results suggest that a broader range of workers are potentially exposed than has been previously examined. These results will allow us to develop a more inclusive exposure assessment encompassing all healthcare workers that are at risk throughout the hospital medication system.